Formula Cerita Detektif dalam Novel Chinmoku no Pareedo - Tiara Rosmika Putri; Fithyani Anwar (J-Litera: Jurnal Kajian Bahasa, Sastra dan Budaya Jepang, 2026)
This study examines the application of John G. Cawelti’s classical detective formula in Keigo Higashino’s Chinmoku no Pareedo. It aims to identify the novel’s narrative structure and analyze its modifications of conventional detective patterns. Using a descriptive qualitative approach, data were collected through close reading and note-taking from narrative passages and dialogues in both the Japanese text and its Indonesian translation. The findings show that the novel employs all five formulaic aspects—introduction of the detective, crime and clues, investigation, solution announcement and explanation, and ending—while introducing major structural variations. The mystery is developed through interconnected cases and flashback sequences, combining genuine and misleading clues embedded in dialogue, character behavior, and past documents. The investigation involves both formal procedures and independent collaboration, with Yukawa acting as a nonconventional detective grounded in logic and scientific reasoning. Overall, the novel demonstrates Higashino’s adaptive use of the classical formula to create a layered and tense detective narrative.